STUDY OF STRUCTURE AND MICROHARDNESS OF PROTECTIVE OXIDECERAMIC COATINGS OBTAINED BY MICRO-ARC OXIDATION ON DEPOSITED SURFACES - Yury Kuznetsov; Aleksey Gribakin; Igor Kravchenko; Vladimir Goncharenko; Alexander Feryabkov4; Alexander Panov; Larisa Kalashnikova (Advanced Engineering Letters)
The paper is devoted to studying the structure and microhardness of protective oxide-ceramic coatings obtained by micro-arc oxidation on the deposited surfaces of parts. Experimental researches were carried out with the use of the commonly used perfected methods and up-to-date measuring instruments and equipment. AlSi7Mg aluminum alloy was used to conduct the research and was deposited with various wires. A welding machine UDG-180 was used to surface the samples. Hardened layers were formed on the deposited surfaces in the developed electrolyte in an installation for micro-arc oxidation, working in the anode-cathode mode. It has been established that the hardened layer formed by micro-arc oxidation is characterized by high microhardness. The increased microhardness of coatings is explained by the presence in their structure of high-temperature solid-phase modification α-Al2O3. Introducing electrolytes of composite materials 1.5 to 1.8 times allows for shortening the oxidation duration. Coatings obtained by micro-arc oxidation are heterogeneous in thickness and physical properties. Considering mechanical processing, the thickness of the hardened layer formed on the deposited surface of the part must be at least 90-120 µm.